Shared Decision Making Needs a Communication Record - KANE, BRIDGET; LUZ, SATURNINO (ACM, 2013)
Increasing dependability in collaboration work among health professionals will directly improve patient outcomes, and reduce healthcare costs. Our research examines the development of a shared visual display to facilitate data entry and validation of an electronic record during multidisciplinary team meeting discussion, where specialists discuss patient symptoms, test results, and image findings. The problem of gen- erating an electronic record for patient files that will serve as a record of collaboration, communication and a guide for later tasks is addressed through use of the shared visual display. Shortcomings in user-informed designed, structured data-entry screens became evident when in actual use. Time constraints prompt the synopsis of discussion in acronyms, free text, abbreviations, and the use of inferences. We demonstrate how common ground, team cohesiveness and the use of a shared visual display can improve dependability, but these factors can also provide a false sense of security and increase vulnerability in the patient management system.
Computer Supported Cooperative Work
PUBLISHED
Increasing dependability in collaboration work among health professionals will directly improve patient outcomes, and reduce healthcare costs. Our research examines the development of a shared visual display to facilitate data entry and validation of an electronic record during multidisciplinary team meeting discussion, where specialists discuss patient symptoms, test results, and image findings. The problem of generating an electronic record for patient files that will serve as a record of collaboration, communication and a guide for later tasks is addressed through use of the shared visual display. Shortcomings in user-informed designed, structured data-entry screens became evident when in actual use. Time constraints prompt the synopsis of discussion in acronyms, free text, abbreviations, and the use of inferences. We demonstrate how common ground, team cohesiveness and the use of a shared visual display can improve dependability, but these factors can also provide a false sense of security and increase vulnerability in the patient management system.
San Antonio, Texas, USA
Keywords: CSCW; Meeting Records; Teamwork; Collaboration; Cancer; Intelligent Content & Communications